2011
DOI: 10.1007/s13187-011-0288-x
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Program in Collaboration with African American Churches Successfully Increases Awareness of the Importance of Cancer Research and Participation in Cancer Translational Research Studies among African Americans

Abstract: African Americans are underrepresented in cancer research. We evaluate whether collaboration with African American churches can improve cancer awareness and increase participation in translational research protocols among African Americans. From February to April 2010, the Mayo Clinic partnered with African American Jacksonville churches to provide educational programs focused on cancer research and healthy behaviors. Education on multiple myeloma and on-site access to a translational cancer research pilot pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Prior research has shown that free healthcare may motivate African Americans’ participation in research, 79 particularly because there is a disparity in health insurance coverage among African Americans compared to their White counterparts. 75, 79 Colon-Otero and colleagues specifically noted that national healthcare reform that ensures universal healthcare coverage will diminish barriers to cancer clinical trial enrollment that uninsured and underinsured patients encounter. 79 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has shown that free healthcare may motivate African Americans’ participation in research, 79 particularly because there is a disparity in health insurance coverage among African Americans compared to their White counterparts. 75, 79 Colon-Otero and colleagues specifically noted that national healthcare reform that ensures universal healthcare coverage will diminish barriers to cancer clinical trial enrollment that uninsured and underinsured patients encounter. 79 …”
Section: Discussionmentioning
confidence: 99%
“…75, 79 Colon-Otero and colleagues specifically noted that national healthcare reform that ensures universal healthcare coverage will diminish barriers to cancer clinical trial enrollment that uninsured and underinsured patients encounter. 79 …”
Section: Discussionmentioning
confidence: 99%
“…This project was part of a Mayo Clinic Institutional Review Board-approved translational cancer research pilot study aimed at increasing awareness on the importance of cancer research among the Northeast Florida AA population [10,11]. The study took place in AA churches located in Northeast Florida and at the Volunteers in Medicine Clinic, a clinic that serves low-income, working, uninsured patients and is located in inner-city Jacksonville, Florida [10,11].…”
Section: Methodsmentioning
confidence: 99%
“…The study took place in AA churches located in Northeast Florida and at the Volunteers in Medicine Clinic, a clinic that serves low-income, working, uninsured patients and is located in inner-city Jacksonville, Florida [10,11]. Blood samples were collected from consented adult subjects during educational sessions in a mobile research unit, a converted recreational vehicle that has sample collection, processing, and storage capabilities [11]. All samples were collected, stored, and transported back to Mayo Clinic in the mobile research unit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation